Use the point-slope form of a line given by:
y−y1=m(x−x1)

Let (x1,y1)=(3,−4) and (x2,y2)=(7,0), the x-intercept so that the slope is: \(\displaystyle{m}=\frac{{{y}{2}-{y}{1}}}{{{x}{2}-{x}{1}}}=\frac{{{0}-{\left(-{4}\right)}}}{{{7}-{3}}}=\frac{{4}}{{4}}={1}\)

So, the equation is:

y−(−4)=1(x−3)

y+4=x−3

y=x−7

Let (x1,y1)=(3,−4) and (x2,y2)=(7,0), the x-intercept so that the slope is: \(\displaystyle{m}=\frac{{{y}{2}-{y}{1}}}{{{x}{2}-{x}{1}}}=\frac{{{0}-{\left(-{4}\right)}}}{{{7}-{3}}}=\frac{{4}}{{4}}={1}\)

So, the equation is:

y−(−4)=1(x−3)

y+4=x−3

y=x−7